2007
DOI: 10.1111/j.1365-2958.2007.05725.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a TFIIH homologue fromTrypanosoma brucei

Abstract: SummaryTrypanosomes are protozoans showing unique transcription characteristics. We describe in Trypanosoma brucei a complex homologous to TFIIH, a multisubunit transcription factor involved in the control of transcription by RNA Pol I and RNA Pol II, but also in DNA repair and cell cycle control. Bioinformatics analyses allowed the detection of five genes encoding four putative core TFIIH subunits (TbXPD, TbXPB, Tbp44, Tbp52), including a novel XPB variant, TbXPBz. In all cases sequences known to be important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 80 publications
4
38
2
Order By: Relevance
“…Another observation was that the TFIIH signal appeared to be present in the nucleolar area, which by DAPI staining is apparent as a spherical structure with reduced staining, whereas the Med-T signal always was excluded from this area. This finding supports a previous study in which the silencing of the TFIIH subunit gene XPD affected nucleolusbased RNA pol I-mediated transcription (26). Med-T is essential for parasite viability and important for SLRNA transcription in vivo.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Another observation was that the TFIIH signal appeared to be present in the nucleolar area, which by DAPI staining is apparent as a spherical structure with reduced staining, whereas the Med-T signal always was excluded from this area. This finding supports a previous study in which the silencing of the TFIIH subunit gene XPD affected nucleolusbased RNA pol I-mediated transcription (26). Med-T is essential for parasite viability and important for SLRNA transcription in vivo.…”
Section: Resultssupporting
confidence: 81%
“…The identification of TFIIA-2 and TFIIB suggested that trypanosomes harbor a full set of GTFs. Accordingly, TFIIH was found to be indispensable for SLRNA transcription (26,28).…”
mentioning
confidence: 99%
“…Similar cytological phenotypes result from blocking various processes. These include knockdowns of a mitotic cyclin or subunits of the transcription factor IIH (TFIIH) homolog in PF T. brucei (Hammarton et al 2003;Tu et al 2006;Lecordier et al 2007). Repression of a PHO80 homolog (CycE1/CYC2) results in cell cycle arrest at the G 1 /S checkpoint and generates slender zoids of T. brucei, while repression of a B-type cyclin homolog (CycB2) results in cell cycle arrest at the G 2 /M transition and generates stumpy zoids (Li and Wang 2003).…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The second subcomplex, called the cyclin-activating kinase complex, contains CDK7-cyclin H and the Mat1 protein. The trypanosome TFIIH core complex has been partially characterized by two groups (32,33). The XPD subunit was identified by bioinformatics, and then tightly associated proteins were analyzed using TAP-tagged, XPD-containing T. brucei cell lines.…”
Section: General Transcription Factors In Trypanosome Rna Pol Ii-depementioning
confidence: 99%